Maps of experience : the anchoring of land to story in Secwepemc discourse - Palmer, Andie Diane N. (University of Toronto Press, 2005)
Palmer's analysis of ways of listening and conveying information within the Alkali Lake community brings new insights into indigenous language and culture, as well as to the study of oral history, ethnohistory, experimental ethnography, and discourse analysis.
Keywords: Shuswap Indians -- History.; Oral tradition -- British Columbia -- Alkali Lake Region (Cariboo); Alkali Lake Indian Reserve No. 1 (B.C.); Secwepemc -- Histoire.; Tradition orale -- Colombie-Britannique -- Alkali, Région du lac (Cariboo); Alkali Lake no 1 (C.-B. : Réserve indienne); HISTORY -- Canada -- General.; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies.; Oral tradition; Shuswap Indians; Shuswap.; Electronic books.; History